2017
DOI: 10.5144/0256-4947.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric cutoff values for predicting metabolic syndrome in a Saudi community: from the SAUDI-DM study

Abstract: BACKGROUNDThe prevalence of metabolic syndrome varies widely by ethnicity and by the criteria used in its definition.OBJECTIVETo identify the optimal cutoff values for waist circumference (WC), waist-to-hip ratio (WHR) and body mass index (BMI) for identifying metabolic syndrome among the Saudi population.DESIGNNationwide household cross-sectional population-based survey.SETTINGThirteen health sectors in Saudi Arabia.SUBJECTS AND METHODSWe used data for subjects in the Saudi Abnormal Glucose Metabolism and Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
3
18
1
Order By: Relevance
“…Our results also showed that the cut-off values of WC for detecting the components of metabolic syndrome ranged from 82.1 to 96 cm for females and 85.3 to 96 cm for males. Similarly, the cut-off values of WHR for detecting the components of metabolic syndrome for women ranged from 0.78 to 0.89; while that of men ranged from 0.86 to 0.95, which is very close to the reports of other studies [ 45 , 48 ]. The optimal cut-off values for WC and WHR were 92 cm, 0.89, for men and 87 cm, 0.81 and for women for identifying the risk of metabolic syndrome in Saudi Arabia [ 48 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our results also showed that the cut-off values of WC for detecting the components of metabolic syndrome ranged from 82.1 to 96 cm for females and 85.3 to 96 cm for males. Similarly, the cut-off values of WHR for detecting the components of metabolic syndrome for women ranged from 0.78 to 0.89; while that of men ranged from 0.86 to 0.95, which is very close to the reports of other studies [ 45 , 48 ]. The optimal cut-off values for WC and WHR were 92 cm, 0.89, for men and 87 cm, 0.81 and for women for identifying the risk of metabolic syndrome in Saudi Arabia [ 48 ].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, with such a high prevalence of the various components of metabolic syndrome, the prevalence of metabolic syndrome in Saudi Arabia would be expected to exceed that is reported in other countries. The current study shows the prevalence of metabolic syndrome in Saudi Arabia to be 39.8% according to the ATP III criteria and 31.6% according to the IDF criteria, when local waist circumference cutoff values have been implemented [ 16 ]. Gulf countries that have passed through similar socio-economic transitions have also shown similar levels of prevalence of metabolic syndrome, in spite of the use of lower cutoff values for waist circumference in both men and women in the current study [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the waist circumference cutoff values that were used for men in the community under study were lower than those proposed by the ATP III and IDF [ 2 , 3 ]. However, this was not the case for women, as the waist circumference cutoff values used for Saudi women were higher than those specified by the IDF criteria, and closer to those of the ATP III criteria [ 16 ]. Another reason behind the low prevalence of metabolic syndrome among women in Saudi society is the lower rate of smoking among Saudi women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of obesity in Saudi Arabia has been reported as 39.3% following the ATP III criteria additionally the prevalence of other parameters for metabolic syndrome has been reached to the apex in the kingdom [15,16]. Saudi Arabia has been considered worldwide as the country with high prevalence of diabetes and in the same manner the obesity has the direct effect on more than 1/3 adolescent population [17]. The recent study is designed to understand the prevalence of metabolic syndrome, association with obesity and risk factors in adolescent population of Al-Dawadmi and Shaqra Region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%